Quantitative Geomorphology Approach in the Assessment of Relative Tectonic Activity in Cikandang Watershed, South West Java - Fahira, Ghina; Sukiyah, Emi; Muslim, Dicky (GEOID, 2025)
Cikandang Watershed in Cisewu Block, South West Java, is an area with significant tectonic activity that is reflected in geomorphological characteristics. This study aims to evaluate the relative tectonic activity in the Cikandang watershed using a quantitative geomorphological approach. Research methods involved six morphotectonic parameters: Valley Height-Width Ratio (Vf), Mountain Face Sinusity (Smf), Basin Shape Index (Bs), Asymmetry Factor (Af), Integral Hypsometry (Hi), and River Length Gradient Index (SL). These parameters were analysed to determine the Index of Relative Tectonic Activity (IATR) in 45 3rd-order catchments. Results showed variations in the level of tectonic activity in the Cikandang watershed. Based on the Index of Relative Tectonic Activity (IATR) value, 6 catchments belong to the high tectonic class, 34 catchments are in the medium tectonic class, and 5 catchments are in the low tectonic class. Analysis results indicate the presence of intensive tectonic deformation. These distributions reflect the significant influence of ‘moderate’ tectonic activity which is also indicated by the role of erosional processes in shaping the geomorphology of the Cikandang watershed. Morphotectonic features such as V-shaped valleys and irregular drainage patterns support the indication of tectonic activity. This research provides an overview of the influence of tectonic activity on geomorphological development in the Cikandang watershed.